2006
DOI: 10.1101/gad.1426906
|View full text |Cite
|
Sign up to set email alerts
|

An MMP liberates the Ninjurin A ectodomain to signal a lossof cell adhesion

Abstract: Matrix metalloproteinases (MMPs) are important for developmental tissue remodeling and for the inflammatory response. Although the vertebrate MMP family is large and functionally redundant, the fruitfly Drosophila melanogaster has only two MMPs, both essential genes. Our previous work demonstrated that Mmp1 is required for growth of the tracheal system, and we suggested that the mutant phenotype resulted from aberrant persistence of cell adhesion to the extracellular matrix. Here we report the identification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 40 publications
5
60
1
2
Order By: Relevance
“…Recently, a new signalling protein that is likely to participate in the normal remodelling of the tracheal tubes was identified 78 . This signalling protein, Ninjurin A, physically associates with DmMMP1 and colocalizes with it at tracheal cell surfaces.…”
Section: Loss Of Dmmmp1 Results In Defects In Tracheal Remodelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a new signalling protein that is likely to participate in the normal remodelling of the tracheal tubes was identified 78 . This signalling protein, Ninjurin A, physically associates with DmMMP1 and colocalizes with it at tracheal cell surfaces.…”
Section: Loss Of Dmmmp1 Results In Defects In Tracheal Remodelingmentioning
confidence: 99%
“…In cell culture, the Ninjurin A ectodomain is shed by DmMMP1 protein, and the liberated ectodomain signals cells to release adhesion. It is likely that in larvae, DmMMP1 releases the Ninjurin A ectodomain, which signals a release of cell adhesion from the tracheal cuticle 78 . The Ninjurin-family proteins were first identified because of their upregulation in injured rat neurons.…”
Section: Loss Of Dmmmp1 Results In Defects In Tracheal Remodelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary antibody stains were done at 4°overnight, and secondary antibody stains were done at room temperature for 4 hr. Primary antibodies used were rat anti-Elav 1:50 Developmental Studies Hybridoma Bank (DSHB), rabbit anti-aPKC (Santa Cruz) 1:1000, mouse anti-Dlg (DSHB) 1:100, and mouse anti-Mmp1 1:100 (DSHB) (Zhang et al 2006). Secondary antibodies from Molecular Probes (Eugene, OR) were anti-rat Alexa488, anti-rabbit Alexa488, and anti-mouse Alexa647, all used at 1:200.…”
Section: Methodsmentioning
confidence: 99%
“…18,[21][22][23] Recently, it has been reported that Drosophila NijA (a fly homolog of vertebrate Ninj1) regulates the remodeling of the tracheal system through interaction with matrix metalloproteinase 1 (MMP1), suggesting that it may be involved in the process of vascular remodeling in higher vertebrates. 24 In this study, we…”
mentioning
confidence: 95%